Evaluation of 23 November 2022 Düzce Earthquake in terms of Regional Seismicity and Strong Ground Motions - Bayrak, Erdem; Çoban, Kaan Hakan (Fırat University, 2024)
The earthquake with a moment magnitude (Mw) of 6.0 occurred in Gölyaka district of Düzce province at 04:08 on November 23, 2022. The earthquake was strongly felt mainly in Düzce province, but also in the Black Sea, Marmara and Central Anatolia regions. As a result of this moderate magnitude earthquake, the peak ground acceleration was recorded as 592 gal at the East-West component of station 8105, about 14 km away. Firstly, the temporal and spatial variation of earthquakes occurring in the region before the 2022 Düzce earthquake was analyzed. Aftershocks occurring after the mainshock were analyzed with the help of the Gutenberg-Richter relationship and the seismicity of the region was revealed. The peak ground accelerations obtained from ground motion prediction equations are compared with the peak ground accelerations recorded at strong ground motion stations. In addition, the response spectra obtained from the acceleration records are compared with the design response spectra obtained according to the Turkish Building Earthquake Code. It was observed that the maximum acceleration values obtained at some stations exceeded the acceleration values calculated with the ground motion prediction equation. It was also observed that the response spectra obtained from the acceleration records exceeded the design spectrum levels calculated according to the Turkish Building Earthquake Code.

Düzce ili Gölyaka ilçesinde 23 Kasım 2022 tarihinde TSİ 04:08’de moment büyüklüğü (Mw) 6,0 olan orta büyüklükte bir deprem meydana gelmiştir. Deprem başta Düzce ili olmak üzere Karadeniz, Marmara ve İç Anadolu bölgelerinde de şiddetli bir şekilde hissedilmiştir. Orta büyüklükte meydana gelen bu deprem sonucunda en büyük yer ivmesi yaklaşık 14 km uzaklıktaki 8105 istasyonunun Doğu-Batı bileşeninde 592 gal olarak kaydedilmiştir. Bu çalışma kapsamında ilk olarak 2022 Düzce depremi öncesi bölgede meydana gelen depremlerin zamansal ve mekânsal değişimi incelenmiştir. Anaşok sonrası meydana gelen artçı şoklar ise Gutenberg-Richter ilişkisi yardımı ile incelenerek bölgenin depremselliği ortaya konulmuştur. Daha sonra, yer hareketi tahmin denklemleri ile hesaplanan en büyük yer ivmeleri ile kuvvetli yer hareketi istasyonlarında kaydedilen en büyük yer ivmeleri karşılaştırılmıştır. Ayrıca ivme kayıtlarından elde edilen tepki spektrumları ile Türkiye Bina Deprem Yönetmeliğine göre elde edilen tasarım tepki spektrumları karşılaştırılmıştır. Bazı istasyonlarda elde edilen en büyük ivme değerlerinin yer hareketi tahmin denklemi ile hesaplanan ivme değerlerini aştığı gözlenmiştir. İvme kayıtlarından elde edilen tepki spektrumlarının da Türkiye Bina Deprem Yönetmeliği’ne göre hesaplanan tasarım spektrum seviyelerini aştığı görülmüştür.
23 Kasım 2022 Düzce Depreminin (Mw 6,0) Bölgesel Sismisite ve Kuvvetli Yer Hareketleri Açısından Değerlendirilmesi
Keywords: Earthquake Engineering; Deprem Mühendisliği; Seismology; Sismoloji